Bioassay-guided fractionation of Artemisia afra for in vitro antimalarial activity against Plasmodium falciparum - Abrahams, Meryl Arlene (Division of Clinical Pharmacology, 2017)
With the increase in recent years in the prevalence of malaria, and in drug resistance of Plasmodium falciparum, there has been much interest in natural plant products for new antimalarials with novel modes of action against Plasmodium. Artemisinin or Qinghaosu is one such antimalarial isolated from a Chinese herb, Anemisia annua (Asteraceae) and it is currently undergoing phase I and II clinical trials. The Southern African species, Artemisia afra (African wormwood, wildeals, lengana) is commonly used by local traditional healers for symptoms of malaria, in particular fever. Thus it seemed appropriate to investigate this species for antimalarial activity. Crude petroleum ether soxhlet extracts of Anemisia afra had demonstrated antimalarial activity against Plasmodium falciparum, FCR-3, cultured in vitro. The IC₅₀ values ranged from 5-13μg/ml. The extract from leaves and flowers was then screened against D10 (chloroquine-sensitive) and FAC8 (chloroquineresistant) P. falciparum, in vitro, with IC₅₀ values of 1.03μg/ml and l.5μg/ml respectively. This extract was fractionated by column chromatography using silica gel-60 and the fractions obtained were screened for antimalarial activity. The most active fraction had an IC₅₀ of 0.5μg/ml against D10 and FAC8. Using TLC and HPLC-UV analysis with pure artemisinin as a standard, no artemisinin could be detected in this fraction. This result was confirmed by thermospray LC-MS analyses. Purification of this fraction yielded ultimately a single pure compound; a clear colourless oil identified by MS and NMR analyses as hydroxydavanone. The compound was screened against a variety of P. falciparum strains with varying degrees of sensitivity and resistance to both chloroquine and mefloquine. Their sensitivity against artemisinin was also established. IC₅₀ values obtained for the isolated pure compound against P. falciparum ranged from 0.87 to 2.54μg/ml. The IC₅₀ values obtained for general cytotoxicity of the crude extract and isolated pure compound against RAT-I fibroblast cells were 34.78 ± 8.23 and 6.29 ± 0.95 μg/ml (n=4) respectively. Thus the crude extract and isolated pure compound exhibited a greater antimalarial than cytotoxic effect. Hence, there are implications for A. afra to be used as a phytomedicine for the treatment of malaria. In vivo studies are recommended for hydroxydavanone in order to fully assess its potential for clinical use.